The faith and doubt of Holocaust survivors - Brenner, Reeve Robert (The Free Press [u.a.], 1980)
Questioning over 1, 000 survivors, Brenner seeks to establish the impact of the Holocaust on the religious belief of those who survived. includes bibliographical references and index.